The real North Korea: life and politics in the failed Stalinist utopia - Lankov, Andrei (Oxford University Press, 2015)
"Andrei Lankov has gone where few outsiders have ever been. A native of the former Soviet Union, he lived as an exchange student in North Korea in the 1980s. He has studied it for his entire career, using his fluency in Korean and personal contacts to build a rich, nuanced understanding. In The Real North Korea, Lankov substitutes cold, clear analysis for the overheated rhetoric surrounding this opaque police state. After providing an accessible history of the nation, he turns his focus to what North Korea is, what its leadership thinks, and how its people cope with living in such an oppressive and poor place. He argues that North Korea is not irrational, and nothing shows this better than its continuing survival against all odds. A living political fossil, it clings to existence in the face of limited resources and a zombie economy, manipulating great powers despite its weakness. Its leaders are not ideological zealots or madmen, but perhaps the best practitioners of Machiavellian politics that can be found in the modern world. Even though they preside over a failed state, they have successfully used diplomacy-including nuclear threats-to extract support from other nations. But while the people in charge have been ruthless and successful in holding on to power, Lankov goes on to argue that this cannot continue forever, since the old system is slowly falling apart. In the long run, with or without reform, the regime is unsustainable. Lankov contends that reforms, if attempted, will trigger a dramatic implosion of the regime. They will not prolong its existence. Based on vast expertise, this book reveals how average North Koreans live, how their leaders rule, and how both survive"--